Parkinsonian Neurotoxins Impair the Pro-inflammatory Response of Glial Cells - Rabaneda-Lombarte, Neus; Xicoy-Espaulella, Efren; Serratosa, Joan; Saura, Josep; Solà, Carme (Frontiers in Molecular Neuroscience, 2019)
In the case of Parkinson’s disease (PD), epidemiological studies have reported that pesticide exposure is a risk factor for its pathology. It has been suggested that some chemical agents, such as rotenone and paraquat, that inhibit the mitochondrial respiratory chain (in the same way as the PD mimetic toxin 1-methyl-4-phenylpyridinium, MPP+) are involved in the development of PD. However, although the neurotoxic effect of such compounds has been widely reported using in vivo and in vitro experimental approaches, their direct effect on the glial cells remains poorly characterized. In addition, the extent to which these toxins interfere with the immune response of the glial cells, is also underexplored. We used mouse primary mixed glial and microglial cultures to study the effect of MPP+ and rotenone on glial activation, in the absence and the presence of a pro-inflammatory stimulus (lipopolysaccharide plus interferon-γ, LPS+IFN-γ). We determined the mRNA expression of the effector molecules that participate in the inflammatory response (pro-inflammatory cytokines and enzymes), as well as the nitric oxide (NO) and cytokine production. We also studied the phagocytic activity of the microglial cells. In addition, we evaluated the metabolic changes associated with the observed effects, through the measurement of adenosine triphosphate (ATP) production and the expression of genes involved in the control of metabolic pathways. We observed that exposure of the glial cultures to the neurotoxins, especially rotenone, impaired the pro-inflammatory response induced by LPS/IFN-γ. MPP+ and rotenone also impaired the phagocytic activity of the microglial cells, and this effect was potentiated in the presence of LPS/IFN-γ. The deficit in ATP production that was detected, mainly in MPP+ and rotenone-treated mixed glial cultures, may be responsible for the effects observed. These results show that the response of glial cells to a pro-inflammatory challenge is altered in the presence of toxins inhibiting mitochondrial respiratory chain activity, suggesting that the glial immune response is impaired by such agents. This may have relevant consequences for brain function and the central nervous system’s (CNS’s) response to insults.